Acceptance and use of mobile health technology in post-abortion care - Zahra Zolfaqari; Haleh Ayatollahi; Fahimeh Ranjbar; Arezoo Abasi (BMC, 2024)
Abstract Background Abortion and its complications have always been associated with challenges such as the lack of awareness, high cost of receiving in-person services, lack of access to the skilled healthcare workers, distance from healthcare centers in remote areas, and cultural sensitivities. Therefore, the use of mobile health technology in post-abortion care has been suggested. This study aimed to investigate factors influencing the acceptance and use of mhealth technology in post-abortion care. Method A mixed-methods study was completed in 2023. Initially, a literature review was conducted. Then, a five-point Likert-scale questionnaire was designed based on the results of the literature review. The research participants were gynecologists (n = 24), midwives (n = 38), and women who had experience of abortion (n = 183). Data were analyzed using descriptive and inferential statistics. Results The findings revealed that the participants had different opinions about the importance of motivating and inhibiting factors which included individual, technical, economic, organizational, and ethico-legal aspects. It seems that the individual, organizational, economic, and ethico-legal motivating factors as well as the ethico-legal inhibiting factors were more important than other factors and had higher mean values. In addition, there was a statistically significant difference between the mean values of gynecologists and patients regarding the individual motivating (P = 0.014) and technical inhibiting factors (P = 0.016). The gynecologists' opinions regarding the technical motivating factors were also significantly different from midwives (P = 0.044) and patients (P = 0.010). Conclusion Multiple factors may influence the acceptance and use of mhealth technology in post-abortion care. Therefore, mhealth service developers must consider these factors to improve the quality of services and increase technology adoption. This will lead to saving costs, improving health, reducing abortion complications, and ultimately improving quality of life for women. However, further research in patient engagement and health interventions tailored to diverse cultural contexts are recommended.